Determination of the Main Phase Transition Temperature of Phospholipids by Oscillatory Rheology - Lívia Budai; Marianna Budai; Tamás Bozó; Gergely Agócs; Miklós Kellermayer; István Antal (Molecules, 2023)
Knowledge of the physical and chemical properties of phospholipids, such as phase transition temperatures (Tc), is of great importance in order to reveal the functionalities of biological and artificial membranes. Our research group developed an oscillatory rheological method for the simple and rapid determination of phase transition temperatures (Tc). The phospholipids constructing the membranes undergo conformational changes at their Tc, which cause alterations of viscoelastic properties of the molecules. The oscillatory technique recommended by us proved to be appropriate to reveal the altered molecular properties of phospholipids as tracking the slightest changes in the viscoelasticity. Our study demonstrates the abrupt changes in rheological properties at Tc for the following phospholipids: 1,2-Dimyristoyl-sn-glycero-3-Phosphocholine (DMPC), 1,2-Dipalmitoyl-sn-glycero-3-Phosphatidylcholine (DPPC), and 1,2-Distearoyl-sn-glycero-3-Phosphocholine (DSPC), proving that the applied methodology is adequate for determining the Tc of phospholipids.